ANALYSIS OF TEACHER COMPETENCE IN IMPROVING READING SKILLS AT KEDUNGRAWAN 2 PRIMARY SCHOOL - Nike Trisna Lailatul Rahmadani; Muhammad Yusuf Afandi; Sindy Olivia Putri; Siti Apriliah; Enik Setyawati (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
This study aims to improve reading skills in students at SDN Kedungrawan 2 in order to make it easier for students to gain insight and learning information through routine activities carried out every morning before learning activities take place. The method used in this research is descriptive qualitative method where researchers conduct observations and interviews to obtain the desired data in accordance with the objectives at the beginning. The results obtained in this study show that the reading activity only runs in one class, namely class 2 where the teacher carries out the habit with independent initiative and is followed by all grade 2 students.